Thermodynamic analysis and nanoparticle assessment of Japanese diesel no 2 fueled truck engine. (July 2018) - Yildiz, Ibrahim; Caliskan, Hakan; Mori, Kazutoshi
Abstract: There are two Japanese quality standards for diesel fuels. One of them is JIS K 2204 class which consists of five class diesel fuels as No. 1, No. 2, No. 3, Special No. 1 and Special No. 3 (1S, 1, 2, 3 and 3S, respectively). No. 2 diesel fuel is generally used for highway vehicles (passenger cars, buses and trucks). In this study, Japanese Industrial Standard Diesel No:2 fuel is utilized to run the truck engine under 284.39 Nm load. The thermodynamic analysis and experimental tests are performed to the engine for nano-particle, emission and efficiency assessments. In this regard, the maximum energy rate is found for the energy of fuel (145.209 kW) which is the main component to start the engine. Also, the minimum energy rate is determined for the exhaust gases which are released to the atmosphere. The power of the truck engine is calculated as 53.585 kW and the energy efficiency is found as 31.625%. Furthermore, the maximum particle concentration is determined around 10 6 1/cm 3 which is lower than other fuels that compared in this study, and the particle size is measured between 5 nm and 15 nm by using Scanning Mobility Particle Sizer (SMPS).